Efficacy of herbicide combinations for weed management in transplanted rice - Menon, Meera V; Bridgit, T. K.; Girija, T. (Journal of Tropical Agriculture, 2017)
An experiment was conducted in farmer’s field at Alappad kole in Thrissur district to evaluate the bio efficacy of herbicide combinations for broad spectrum weed control. The treatments were : post-emergence application of bispyribac-sodium 25 g ha-1, penoxsulam 24% SC 22.5 g ha-1, bispyribac-sodium 25 g ha-1 + ethoxy sulfuron 18.75 g ha-1, bispyribac- sodium 25 g ha-1 + premix of (chlorimuron-ethyl and metsulfuronmethyl) 4 g ha-1, pre-emergence application of pretilachlor 750 g ha-1 followed by (fb) post-emergence application of ethoxy sulfuron 18.75 g ha-1, re-emergence application of pretilachlor 750 g ha-1 fb postemergence application of premix of (chlorimuron-ethyl and metsulfuron-methyl) 4 g ha-1, pre-emergence application of pyrazosulfuron ethyl 20 g ha-1 fb post-emergence application of premix of (chlorimuronethyl and metsulfuron-methyl) 4 g ha-1, post-emergence application of premix of penoxsulam + cyahalofopbutyl 6% OD 135 g ha-1, post-emergence application of premix of triafamone + ethoxy sulfuron 60 g ha-1, pre-emergence application of pendimethalin 750 g ha-1 fb post-emergence application of bispyribac-sodium 25 g ha-1, hand weeding at 25 and 45 DAT and weedy check. Hand weeding resulted in highest weed control and grain yield. Among the herbicide combinations, lowest weed dry matter production and weed control efficiency, and highest grain yield were recorded by triafamone combined with ethoxy sulfuron, and bispyribac- sodium combined with premix of (chlorimuron-ethyl + metsulfuron- ethyl). All treatments were significantly superior to unweeded control.